Processing and Arduino in Tandem creating your own digital art tools - Gray, Joseph; Safari eBooks ([S.l.] : creativeLIVE and O'Reilly Media, 2010)
"The projBox Kit contains everything you need to follow along with Processing and Arduino in Tandem. The kit, which requires no soldering, is ideal for beginners in electronics and physical computing."
System requirements: Adobe Flash Player, version 8 or higher.
Title from resource description page (viewed Oct. 13, 2010).
Keywords: Processing (Computer program language); Digital art; Computer animation; Open source software; Electronic books